Pemanfaatan Potensi Energi Aliran Kanal Kalisolo I pada Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi - Ahmad Nawawi; Sonden Winarto (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2019)
Energy needs to improve services and operations in every office are needed, as well as infrastructure for oil and gas PPSDM infrastructure; Office, laboratory, housing and processing facilities are reported. Along with operational costs that increase in terms of energy costs, which include electricity, air and fuel oil. Oil and Gas PPSDM can request operational costs. The utilization of this energy can simultaneously participate in government programs to develop new renewable energy, as well as a pilot project for the community to use waste energy. To fulfill the need for clean water in Oil and Gas PPSDM, which on average every meeting requires water of 3,250 m3, using air from Bengawan Solo, which is processed in the air treatment section, by pumping and channeling it through the traffic channel to processing tanks. The air flow in this canal requires energy as a power plant. In this research, the installation of Kalisolo 1 Oil and Gas PPSDM Channel was installed for Hydrokinetic Power Plant (PLTHk) and / or Micro Hydro Power Plant (PLTMH) using the Open Flume Turbine. After measuring the object and analyzing it, on object I with a cross-sectional area of ​​1 mx 0.35 m, velocity of channel air flow 0.8 m / s, the power potential of 89.6 W. was obtained in object II with a cross-sectional area of ​​0, 4 mx 0.4 m, canal water flow velocity 0.4 m / s, obtained power potential of 5.12 W, if using MHP. While using the Micro Hydro Power Plant (PLTMH) using the Open Flume Turbine, taking into account the 2 m water head, on my object it can produce electric power of 494,424 W or 0.5 kW, and if the air head is 1 m, power can be generated electricity is 247,212 Watt or 0.25 kW, with generator efficiency 0.9 and turbine efficiency of 0.9, while in object II the Turbine Flume PLTMH cannot be regulated, because it is difficult to design head water.